Healing gardens for the elderly: a review of design guidelines and the comparisons with the existing Senior Outdoor Survey (SOS) tool - Chong, Yee Er; Abdul Shukor, Shureen Faris (Faculty of Design & Architecture, Universiti Putra Malaysia, 2016)
This systematic review evaluated 15 literature that discussed design considerations for outdoor areas for the elderly at hospitals, nursing homes, hospices and also public spaces. An existing result from a study to evaluate the outdoor spaces at the elderly’s facilities called Senior Outdoor Survey (SOS) tool was being used to compare with the design recommendations from other literature. The comparison of the SOS tool with the other literature was intended to simplified the guidelines for the design of healing gardens for the elderly. Two types of literature were reviewed in the study which were the peer-reviewed papers and best practice guidelines. Finally, a list of the most essential design features was identified in which may be useful for the health policy makers, hospital administrators and designers who are involved with the outdoor spaces for the elderly. The results have shown that the most essential features to be considered included aspects such as seating, paving material, the activities and, the location of the gardens.